1982
DOI: 10.1111/1523-1747.ep12530360
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glucocorticoids on Glycosaminoglycan Metabolism in Cultured Human Skin Fibroblasts

Abstract: Human skin fibroblasts were exposed to 3 anti-inflammatory steroids in order to study their effects on the glycosaminoglycan metabolism. The potent glucocorticoids, fluocinolone acetonide and budesonide, even at low concentrations strongly reduced the accumulation of hyaluronic acid and sulfated glycosaminoglycans in the medium, at the cell surface, and in the cells. Hydrocortisone had considerably less effect. The 3 compartments were not influenced to the same extent and the least inhibition was noted in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…The immediate-onset skin thinning in duced by CS is due to the fact that the formation of ground substance of the connective tissue -like hyaluronic acidis inhibited [10,11 ]. Katz et al [12] proposed to call this phenomenon preatrophy.…”
Section: Discussionmentioning
confidence: 99%
“…The immediate-onset skin thinning in duced by CS is due to the fact that the formation of ground substance of the connective tissue -like hyaluronic acidis inhibited [10,11 ]. Katz et al [12] proposed to call this phenomenon preatrophy.…”
Section: Discussionmentioning
confidence: 99%
“…The basis of this phenomenon has been inten sively investigated in recent years [2][3][4][5], It is well established that glucocorticoids can inhibit cell proliferation and mitosis [6], decrease collagen [7] and glycosaminoglycan synthesis [8], and general protein production. There is consensus that glucocorticoids direct ly influence the metabolism of dermal fibro blasts.…”
Section: Introductionmentioning
confidence: 99%
“…Sarnstrand et al (23) reported that glucocorticoid treatment not only reduced the quantity of various glycosaminoglycans but also changed the distribution, relative proportion, and structure of connective tissue proteoglycans. These changes may contribute to hyalinization of dermal collagen bundles, which is marked at the sites treated with potent corticosteroids.…”
Section: Histologic Changesmentioning
confidence: 99%